2010
DOI: 10.1093/rheumatology/keq097
|View full text |Cite
|
Sign up to set email alerts
|

Digital ulcers in scleroderma: staging, characteristics and sub-setting through observation of 1614 digital lesions

Abstract: In SSc, digital lesions are represented by DPS, DU, calcinosis and gangrene, and provide an evidence-based DU subsetting according to their origin and main characteristics. Subsetting may be helpful for a precise DU evaluation and staging, and in randomized controlled trials for a precise identification of those DUs that are to be included in therapeutic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
142
3
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(164 citation statements)
references
References 13 publications
2
142
3
12
Order By: Relevance
“…Basic demographic characteristics including age, gender, BMI, systolic and diastolic blood pressure (BP) and HR of the whole population were recorded. Patients with SSc were screened in terms of disease duration (defined as interval between date of diagnosis and inclusion into study), and presence of digital ulcer [16], Raynaud's phenomenon [17] and severity of skin involvement in SSc patients were determined by the modified Rodnan method and modified Rodnan skin severity score (MR-SSS) calculated for all SSc patients. At more detailed method description for MR-SSS can be found in a study reported by Czirjak et al [18].…”
Section: Study Populationmentioning
confidence: 99%
“…Basic demographic characteristics including age, gender, BMI, systolic and diastolic blood pressure (BP) and HR of the whole population were recorded. Patients with SSc were screened in terms of disease duration (defined as interval between date of diagnosis and inclusion into study), and presence of digital ulcer [16], Raynaud's phenomenon [17] and severity of skin involvement in SSc patients were determined by the modified Rodnan method and modified Rodnan skin severity score (MR-SSS) calculated for all SSc patients. At more detailed method description for MR-SSS can be found in a study reported by Czirjak et al [18].…”
Section: Study Populationmentioning
confidence: 99%
“…The DUs were classified according to Amanzi et al as follows: DUs derived from digital pitting scar (DPS), pure DUs, DUs derived from calcinosis, and DUs derived from gangrene (12 …”
Section: Nailfold Videocapillaroscopy (Nvc)mentioning
confidence: 99%
“…Patients very often suffer from small erosions, ulcers and even necrosis of the fingers in rare cases [3,9,10]. Hypoxia is also a main cause of bone resorption and autoamputation of distal phalanges in patients diagnosed with SSc ( Fig.…”
Section: Raynaud's Syndrome -The Secondarymentioning
confidence: 99%